Enhancing methane detection limit of OA-ICOS: a combined approach of white noise perturbation and Savitzky-Golay filtering - Yang, Ce; Chen, Zongheng; Chen, Chen; Li, Chunguang; Liu, Siqing; Huang, Jianyu; Li, Yu; Song, Laiyong; Li, Hongbin (Frontiers in Physics, 2025)
In the context of global clean energy demand and climate change, the dynamic monitoring of methane is crucial for carbon cycle research and greenhouse gas assessment. In order to solve the problem of cavity mode noise limiting measurement performance in the off-axis integrated cavity output spectroscopy (OA-ICOS) system, an optimization method based on white noise injection was proposed. A broadband white noise perturbation is introduced into the distributed feedback (DFB) laser, and the Savitzky-Golay (S-G) filtering algorithm is used to further reduce the noise. It effectively suppresses the coherence of cavity mode noise, reduces the noise floor, and improves the signal-to-noise ratio and measurement sensitivity of the system. Experiments show that when white noise with a modulation depth of 30% is injected, the signal-to-noise ratio of the system is increased by about 3.16 times, and the methane measurement limit is optimized from 5.32 ppm to 2.22 ppm of the original system, which is about 2.4 times. The Allan deviation showed a significant increase in minimum detectable limit. Further verification by methane dynamic test shows that the system response time is about 1 min, showing reliable measurement stability. This study provides an innovative technical solution for high-precision methane measurement, which is of great significance for promoting in-situ greenhouse gas monitoring and climate model optimization.